TEORI DAN PRAKTIK PENDIDIKAN DALAM ISLAM - Sitika, Achmad Junaedi; Salsadilla, Andini Septi; Anggraeni, Dea Dwi; Khasanah, Dhini; Handayani, Firly Aulia; Ramdan, Gilang (Program Pascasarjana UIN Sumatera Utara, 2023)
The Educational Process takes place throughout history and develops in parallel. With the development of social culture, humans on earth develop social culture. The development of human culture originates from the guidelines of Islamic teachings which have been set forth in the Qur'an and al-Hadith. Basically, being an educational staff is a very heavy responsibility that must be carried out because it is related to the gate of the relay of the nation's struggle relay, so that it is free from the crisis of education and the moral degradation of the nation's children. Becoming a teacher is a very tough challenge, because teachers are required to be professional in learning. In continuing with a teacher, the teacher must have a good strategy in carrying out his duties as an educator. The learning strategy is an arrangement of activities that are included in the use of methods and utilization of various resources or strengths in learning. In the explanation above it is explained that functionally a teacher or educator must certainly require broad insight, appropriate theory and practice in his field professionally.